Investigation of DC-Biased Optical OFDM With Precoding Matrix for Visible Light Communications: Theory, Simulations, and Experiments - Tao Jiang; Ming Tang; Rui Lin; Zhenhua Feng; Xi Chen; Lei Deng; Songnian Fu; Xiang Li; Wu Liu; Deming Liu (IEEE Photonics Journal)
Orthogonal frequency-division-multiplexing (OFDM) technology is widely used in visible light communication (VLC) to achieve high data rate transmission. However, the traditional direct-current (DC)-biased optical OFDM (DCO-OFDM) VLC systems suffer from the high peak-to-average power ratio (PAPR) which causes signal clipping distortion, and, thus, performance degradation. Furthermore, severe high-frequency fading due to the limited system bandwidth results in poor bit error rate (BER) performance. Precoding matrix (PM) techniques have been proposed to enhance the performance of VLC OFDM transmission, but a little or no work has been carried out in investigating the theory of PM used in OFDM VLC systems. In this paper, we aim to reveal the theory of PM-DCO-OFDM for a VLC system. To figure out the intrinsic laws of a PM method, we investigate the principles of PAPR reduction, clipping distortion optimization, and signal-to-noise ratio (SNR) distribution equalization. Based on the analysis of PAPR, we theoretically proved the simplicity of PM as a method to reduce the possibility of high PAPR by improving the autocorrelation performance of input symbols. The clipping distortion could be improved due to the reduction of high PAPR. Moreover, the relatively uniform SNR distribution can be achieved by PM through equalizing the clipping and channel noise, which is beneficial to improve the BER performance in high-frequency constrained systems. However, the PM method used in a DCO-OFDM VLC system should consider the transmitting power, modulation format, and transmission distance as a whole to achieve the transmission performance improvement. The simulation results demonstrate the complementary cumulative distribution function of PAPR can be reduced ∼3 dB, while the performance of clipping distortion power and clipping error probability are significantly improved. Furthermore, experiment is carried out with results showing that the PM method can improve the BER performance in the case that VLC OFDM transmission has enough transmitting power, but with the low transmitting power, the PM also can damage the BER performance. The simulation and experiment results are consistent with our theoretical analysis.